Infected Dentigerous Cyst of Maxillary Sinus Mimicking Intraoral Abscess in a Pediatric Patient: Management of Misdiagnosis and Inaccurate Treatment - Damian Chybicki; Alicja Popielarczyk; Wojciech Markowski; Gaja Torbicka; Anna Janas-Naze (Hindawi Limited, 2022)
The article presents the case of a 12-year-old male patient who was suffering from exacerbated (infected) dentigerous cyst of maxillary sinus, associated with impacted canine whose symptoms were deceptively similar to intraoral abscess. The first-aid treatment performed by general dental practitioner consisted of intraoral incision and resulted in oroantral fistula formation. Eventually, the patient's ailments were not resolved, and we had to deal with serious local complications and difficulties. The treatment was performed under general anesthesia in one-day surgery system and included enucleation of the lesion, excision, and closure of oroantral fistula. Dislocated canine was not removed, and its subsequent eruption was observed.